The Significance of Sustainability and Renewable Energy Development in Five North African Countries - Salaheddine Sari-Hassoun,; Hacen Kahwi, (African Journal of Advanced Pure and Applied Sciences, 2024)
In the past ten years, there has been significant progress in two well-known economic concepts: sustainable development and renewable energy. Currently, developing nations are attempting to implement the Sustainable Development Goals by establishing their economies and infrastructure. This article investigates the relationship between adjusted net savings, renewable energy consumption, gross domestic product, and labour force in five North African countries from 2000 to 2022. We demonstrate a positive and significant relationship between REC and ANS, as well as GDP and ANS. On the other hand, LF has a negative and significant effect on ANS. According to this, these countries are ready to invest in RE and create new value-added based on innovative systems, with an emphasis on economic growth and the growth of the primary economic sectors.